Study of the effects of microwave curing on ultra-high-performance concrete based on dielectric properties - Jingyuan Chen; Shuangxin Li; Xiaojian Gao; Xusen Li (Case Studies in Construction Materials)
Microwave curing has emerged as a promising technique to accelerate the hydration process in ultra-high-performance concrete (UHPC), yet its effects on the material dielectric properties and molecular-level polarization remain insufficiently understood. This study investigates the impact of microwave curing on the dielectric properties and molecular polarization behavior of UHPC. UHPC samples were cured under both standard curing (SC) and microwave curing (MC) conditions for 28 days, with an analysis of the dielectric properties throughout the curing period. The correlation between the degree of hydration and the dielectric constant (ε) was explored to understand the influence of microwave curing on the material performance. A molecular dynamics (MD) simulation was employed to model the effect of 2.45 GHz microwave fields on the dielectric properties of calcium-silicate-hydrate (C-S-H), complemented by grey correlation and multi-scale analyses. Results show that microwave time and temperature significantly affect the dielectric constant of UHPC, with the most optimal acceleration effect observed at 30 °C for 0.25 h. A linear relationship between dielectric constants and hydration degrees was established for both SC and MC specimens, indicating that microwaves uniquely influence hydration processes. Molecular dynamics simulations revealed that microwave irradiation enhances the orientational polarization of interlayer molecules in C-S-H, increasing the polarization rate by 1.19 × 10⁻³ D/Å³ under a 0.4 V/nm field strength. This study provides valuable insights into the macroscopic and microscopic effects of microwaves on UHPC, offering theoretical support for advancing microwave curing technology in construction materials.